If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 9x + -7 Reorder the terms: 18 = -7 + 9x Solving 18 = -7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 18 + -9x = -7 + 9x + -9x Combine like terms: 9x + -9x = 0 18 + -9x = -7 + 0 18 + -9x = -7 Add '-18' to each side of the equation. 18 + -18 + -9x = -7 + -18 Combine like terms: 18 + -18 = 0 0 + -9x = -7 + -18 -9x = -7 + -18 Combine like terms: -7 + -18 = -25 -9x = -25 Divide each side by '-9'. x = 2.777777778 Simplifying x = 2.777777778
| L=1+-3w | | 4(4x-4)=-144 | | 5(n)=126 | | 7+4(x-4)-10=-45 | | 3+3x=4x+20 | | 13=×/3-22 | | 50/X-60=51.666 | | 2x-15+3(x-1)=13 | | 2x+3(8)=24 | | 7x-7*2=49 | | y-5=-5.2(x+4) | | 3(n)=1200 | | 6(-9-5x)=-264 | | 7n-3n=4 | | -12=1/8x | | 1(x)=8(40) | | 130=16t*t+27t | | 20m-19m=16 | | -4r-4.7+2.3r+0.3r+5= | | 7=6(x+4)-6 | | 36x-2=4(5+3x) | | 5x^2-8=-12 | | -12x-165+3x=51 | | 22-×/3=13 | | 130=-16t*t+27t | | 15n+11=6 | | 34-13=3(x-6) | | 6z-10z=28 | | -3(-8+5x)=-156 | | 3(c-5)-4=-55 | | 150x^2+10x-8=0 | | 6m+2m=-32 |